2003
DOI: 10.3367/ufnr.0173.200308b.0813
|View full text |Cite
|
Sign up to set email alerts
|

Defect-impurity engineering in implanted silicon

Abstract: ÑÃÓÂÊÑÏ:¬ÂÍ ÔÎÇAEÖÇÕ ËÊ ÖÓÂÄÐÇÐËâ (5), ÒÇÕÎË Ô ÓÂAEËÖÔÑÏ r`" r ËÏÇáÕ ÕÇÐAEÇÐÙËá Í ÔÑÍÓÂÜÇÐËá, ÕÑÅAE ÍÂÍ AEÎâ r b " r ÐÂÃÎáAEÂÇÕÔâ ÓÑÔÕ ÒÇÕÎË. ±ÇÕÎË Ô ÓÂAEËÖÔÑÏ r " r ÐÇ ÓÂÔÕÖÕ Ë ÐÇ ÔÑÍÓÂÜÂáÕÔâ, ÐÑ ÒÑÔÎÇ ËÔÚÇÊÐÑÄÇÐËâ ÒÇÕÇÎß ÏÂÎÑÅÑ ÓÂAEËÖÔ ÄÇÎËÚËР" r ÖÄÇÎËÚËÄÂÇÕÔâ.ªÐÕÇÅÓËÓÑÄÂÐËÇ ÄÞÓÂÉÇÐËâ (5) ÄÇAEÇÕ Í àÄÑÎáÙËË ÍÄÂAEÓÂÕ ÔÓÇAEÐÇÅÑ ÓÂAEËÖÔ ÒÇÕÇÎß ÄÑ ÄÓÇÏÇÐË. ¿ÕÑÕ ÓÑÔÕ ÊÂÒËÔÞÄÂÇÕÔâ ÔÎÇAEÖáÜËÏ ÑÃÓÂÊÑÏ [81]:£ ÔÎÖÚÂÇ, ÍÑÅAE ÒÓÑÙÇÔÔ ÓÑÔÕ ÒÇÕÎË ÍÑÐÕÓÑÎËÓÖÇÕÔâ ÄÇÎËÚËÐÑÌ ÃÂÓßÇӠРÍÎÂÔÕÇÓÇ, ÔÍÑÓÑÔÕß ÖÍÓÖÒÐÇÐËâ K K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 260 publications
0
6
1
1
Order By: Relevance
“…The migration energy of oxygen dimers is 0.8 eV less than that of single oxygen atom [29]. Moreover, according to [28], Si-Si diinterstitials are more mobile than the single Si interstitial atoms. In [30,31], the values of migration energies of the interstitial atom and the vacancy are near 1 eV.…”
Section: Isothermal Annealing Of Si 〈Ge〉mentioning
confidence: 95%
See 1 more Smart Citation
“…The migration energy of oxygen dimers is 0.8 eV less than that of single oxygen atom [29]. Moreover, according to [28], Si-Si diinterstitials are more mobile than the single Si interstitial atoms. In [30,31], the values of migration energies of the interstitial atom and the vacancy are near 1 eV.…”
Section: Isothermal Annealing Of Si 〈Ge〉mentioning
confidence: 95%
“…As shown in [12], oxygen prevents the exit of Si interstitial atoms onto the crystal surface and, probably, is the centre of di-interstitial defect formation. In [28], it was supposed that under a high density of interstitial atoms in the matrix they organize Si-Si pairs. Such pairs are formed as a result of the stochastic location of two silicon atoms into the one interstitial space.…”
Section: Isothermal Annealing Of Si 〈Ge〉mentioning
confidence: 99%
“…Часто при изготовлении полу-проводниковых структур в качестве техноло-гического средства для придания эпитаксиаль-ным слоям необходимых свойств их подверга-ют радиационному облучению или ионизацион-ному воздействию при ионной имплантации [1]. Радиационное воздействие и ионизирующее из-лучение также влияют на характеристики и па-раметры готовых полупроводниковых элемен-тов в процессе их эксплуатации [2].…”
Section: повышение раäиационной óстойчивости êремниевых моноêристаллиunclassified
“…In [4,12] it is concluded that the formation of residual extended defects in silicon needs an dose "threshold". This means that such structural disorder during heat treatment (at least 700°C) arises only if a critical concentration of point defects has accumulated.…”
Section: Introductionmentioning
confidence: 99%